Prevalence and associated factors of physical inactivity among adults in Northwest Ethiopia: a multicenter study - Muche, Zelalem Tilahun; Teklemariam, Awgichew Behaile; Abebe, Endeshaw Chekol; Agidew, Melaku Mekonnen; Ayele, Tekile Mengie; Zewde, Edgeit Abebe; Mulu, Anemut Tilahun; Tiruneh, Gebrehiwot Ayalew; Kefale, Demewoz; Abuhay, Deribew Abebaw; Midekssa, Milkessa Bayissa; Baye, Nega Dagnew (Frontiers in Public Health, 2025)
BackgroundPhysical inactivity (PI) increases the risk of cardiovascular diseases, cancer, diabetes, cognitive impairment, poor sleep, poor bone health, obesity, economic crises, and premature mortality. Globally, 31% of adults are physically inactive, indicating that this is the major public health issue of this century. Physical inactivity prevalence varies among countries, regions, and cities. In addition, data were scarce in the study area.ObjectiveThis study identified the prevalence and determinants of PI among adults in Northwest Ethiopia.MethodA community-based cross-sectional study was conducted from February to March 2024. Participants were recruited via multistage sampling, and the data were collected via WHO stepwise standard questionnaires. Binary and multivariable logistic regressions were used to identify the predictors of physical inactivity.ResultsThis study involved 592 participants, with a mean age of 36.2 ± 12.6 years, 56.4% of whom were males. Nearly three-fourths (71.5%) of the respondents had no awareness of physical activity guidelines. The prevalence of PI was 46.1%. Increasing age, being female, being a government or nongovernment employee, having a high level of education, having a high family monthly income, currently smoking, chewing khat, drinking alcohol, being overweight or obese, unawareness of physical activity guidelines, and lacking a plan to do physical activity were associated with PI.Conclusion46.1% of adults were physically inactive, highlighting a significant public health concern. Thus, we emphasize improving physical activity by promoting its health benefits, raising awareness about the guidelines, and encouraging adults to have a plan to do physical activity.